Prevalence and target attainment of traditional cardiovascular risk factors in patients with systemic lupus erythematosus: a cross-sectional study including 3401 individuals from 24 countries - DİRESKENELİ, RAFİ HANER (My University, 2024)
Background: Systemic lupus erythematosus (SLE) is characterised by increased cardiovascular morbidity and mortality risk. We aimed to examine the prevalence of traditional cardiovascular risk factors and their control in an international survey of patients with systemic lupus erythematosus. Methods: In this multicentre, cross-sectional study, cardiovascular risk factor data from medical files of adult patients (aged ≥18) with SLE followed between Jan 1, 2015, and Jan 1, 2020, were collected from 24 countries, across five continents. We assessed the prevalence and target attainment of cardiovascular risk factors and examined potential differences by country income level and antiphospholipid syndrome coexistence. We used the Systemic Coronary Risk Evaluation algorithm for cardiovascular risk estimation, and the European Society of Cardiology guidelines for assessing cardiovascular risk factor target attainment. People with lived experience were not involved in the research or writing process. Findings: 3401 patients with SLE were included in the study. The median age was 43·0 years (IQR 33–54), 3047 (89·7%) of 3396 patients were women, 349 (10.3%) were men, and 1629 (48·1%) of 3390 were White. 556 (20·7%) of 2681 patients had concomitant antiphospholipid syndrome. We found a high cardiovascular risk factor prevalence (hypertension 1210 [35·6%] of 3398 patients, obesity 751 [23·7%] of 3169 patients, and hyperlipidaemia 650 [19·8%] of 3279 patients), and suboptimal control of modifiable cardiovascular risk factors (blood pressure [target of <130/80 mm Hg], BMI, and lipids) in the entire SLE group. Higher prevalence of cardiovascular risk factors but a better blood pressure (target of <130/80 mm Hg; 54·9% [1170 of 2132 patients] vs 46·8% [519 of 1109 patients]; p<0·0001), and lipid control (75·0% [895 of 1194 patients] vs 51·4% [386 of 751 patients], p<0·0001 for high-density lipoprotein [HDL]; 66·4% [769 of 1158 patients] vs 60·8% [453 of 745 patients], p=0·013 for non-HDL; 80·9% [1017 of 1257 patients] vs 61·4% [486 of 792 patients], p<0·0001 for triglycerides]) was observed in patients from high-income versus those from middle-income countries. Patients with SLE with antiphospholipid syndrome had a higher prevalence of modifiable cardiovascular risk factors, and significantly lower attainment of BMI and lipid targets (for low-density lipoprotein and non-HDL) than patients with SLE without antiphospholipid syndrome. Interpretation: High prevalence and inadequate cardiovascular risk factor control were observed in a large multicentre and multiethnic SLE cohort, especially among patients from middle-income compared with high-income countries and among those with coexistent antiphospholipid syndrome. Increased awareness of cardiovascular disease risk in SLE, especially in the above subgroups, is urgently warranted. Funding: None.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; RHEUMATOLOGY; Romatoloji; İmmünoloji ve Alerji; Rheumatology; Immunology and Allergy; Immunology